Varför är svensk popmusik så populär utomlands? Synpunkter på det ”svenska musikundret” och på det spontana i popmusikens musikaliska språk - Sandgren, Patrik (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2000)
This paper discusses the reasons for the recent success of Swedish popular music abroad. It departs from recent Swedish economic reports showing that the increase in exports of Swedish music per capita is comparable to, and even exceeds, those of the United Kingdom and the United States, and presents theories about why Swedish popular music exports have grown during the last years. A method of musical analysis is presented in this paper with the aim of demonstrating that Swedish popular music contains melodic formulas similar to children’s songs and nursery rhymes. The analyses have a semiotic focus, and place the music itself in a more prominent role than tends to be common within ordinary semiotic analyses of popular music.